Development of Digital Teaching Materials Through Canva and Book Creator for College Students of Elementary Education - Nurlaila Eka Erfiana, Nita Agustina; Rohmah, Liatul (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This research focuses on developing digital teaching materials using Canva and Book Creator specifically for elementary education students at the State Islamic University of Sayyid Ali Rahmatullah Tulungagung. Using a Research and Development (R&D) model, the process unfolds across five key stages: analyze, design, develop, implement, and evaluate. During the analysis stage, it was discovered that 72% of students found traditional materials unappealing, 64% deemed them irrelevant, and 68% felt they did not promote critical thinking. In the design phase, the emphasis was placed on crafting interactive and visually engaging resources, including infographics, videos, and quizzes. As the development stage progressed, teaching resources were validated by design, content, and materials experts. In the implementation phase, 118 students participated in two sessions with pre-test and post-test assessments. The results were encouraging, showing an increase in the average score from 56.53 to 82.50 (N-Gain Score: 0.82). Notably, 82% of students reported that the digital materials were more engaging, while 76% indicated that the interactive features enhanced their comprehension. The evaluation phase revealed that these digital teaching materials significantly improved student understanding and motivation. Feedback from students and lecturers has pointed to areas for further enhancement, such as improving visual quality and integrating more interactive quizzes and instructional videos. Overall, this study underscores the effectiveness of digital teaching materials in boosting learning engagement and supporting their integration into contemporary educational practices.